Phloretin attenuates STAT-3 activity and overcomes sorafenib resistance targeting SHP-1–mediated inhibition of STAT3 and Akt/VEGFR2 pathway in hepatocellular carcinoma - Saraswati, Sarita (Cell Commun Signal, 2019)
BACKGROUND: Hepatocellular carcinoma (HCC) is the most common primary liver malignancy. Phloretin (PH) possesses anticancer, antitumor, and hepatoprotective effects, however, the effects and potential mechanisms of phloretin remain elusive. METHODS: Five HCC cells were tested in vitro for sensitivity to PH, Sorafenib (Sor) or both and the apoptosis, signal transduction and phosphatase activity were analyzed. To validate the role of SHP-1, we used PTP inhibitor III and SHP-1 siRNA. Further, we used purified SHP-1 proteins or HCC cells expressing deletion N-SH2 domain or D61A point mutants to study the PH efficacy on SHP-1. The `in vivo studies were conducted using HepG2 and SK-Hep1 and Sor resistant HepG2(SR) and Huh7(SR) xenografts. Molecular docking was done with Swiss dock and Auto Dock Vina. RESULTS: PH inhibited cell growth and induced apoptosis in all HCC cells by upregulating SHP-1 expression and downregulating STAT3 expression and further inhibited pAKT/pERK signaling. PH activated SHP-1 by disruption of autoinhibition of SHP-1, leading to reduced p-STAT3(Tyr705) level. PH induced apoptosis in two Sor-resistant cell lines and overcome STAT3, AKT, MAPK and VEGFR2 dependent Sor resistance in HCCs. PH potently inhibited tumor growth in both Sor-sensitive and Sor-resistant xenografts in vivo by impairing angiogenesis, cell proliferation and inducing apoptosis via targeting the SHP-1/STAT3 signaling pathway. CONCLUSION: Our data suggest that PH inhibits STAT3 activity in Sor-sensitive and -resistant HCCs via SHP-1–mediated inhibition of STAT3 and AKT/mTOR/JAK2/VEGFR2 pathway. Our results clearly indicate that PH may be a potent reagent for hepatocellular carcinoma and a noveltargeted therapy for further clinical investigations. GRAPHICAL ABSTRACT: [Image: see text] ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12964-019-0430-7) contains supplementary material, which is available to authorized users.